The last great forest Luzon's Northern Sierra Madre Natural Park - Tan, Jose Ma. Lorenzo; Vibar, Ma. Christine R.; Suarez, Luis C.; Altomonte, Carina S.; Tanedo, Vic V. (Makati City, Philippines The Bookmark, Inc., 2000)
Tells the story of of the Northern Sierra Madre Natural Park, recognised as one of the key global sites for conservation of biodiversity, and located along a vast range of mountains down the northeastern flank of Luzon in the Philippines. The park is home to 70 `at risk' species including mammals, birds, amphibians and reptiles, and shellfish, and serves as home to more than a thousand indigenous people, the Dumagats.
Chapter 1: The Natural park -- Chapter 2: The Area and its People -- Chapter 3: Management of the Park -- Chapter 4: Flora -- Chapter 5: Fauna -- Chapter 6: Conservation within the Park -- Chapter 7: What Lies Ahead Things That Must be Done.
Keywords: Rain forests -- Philippines -- Isabela; Rain forest conservation -- Philippines -- Isabela